2019
DOI: 10.1021/acs.jpcc.9b02106
|View full text |Cite
|
Sign up to set email alerts
|

Vibronic Effects in the Ultrafast Interfacial Electron Transfer of Perylene-Sensitized TiO2 Surfaces

Abstract: We combine ultrafast transient absorption (TA) spectroscopy and nonadiabatic quantum dynamics simulations to describe the real-time unfold of vibronic effects on the photoabsorption of TiO 2 anatase sensitized with the (perylen-9-yl)carboxylate dye (Pe-COOH/TiO 2 ). The excited state is mapped in time and frequency by ultrafast broadband spectroscopy while atomistic quantum dynamics is used to simulate the self-consistent vibronic effects. The TA map shows the lifetime of the electronic population generated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…83 In a related study, excited-state injection by (perylene-9yl)carboxylate into TiO 2 was shown to be complete within 12 fs. 84 The ultrafast transient absorption data mapped the decay of the singlet excited state and the appearance of the oxidized perylene. Nonadiabatic quantum dynamic simulations indicated that injection was complete within 20 fs, in close agreement with the experimental value.…”
Section: Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…83 In a related study, excited-state injection by (perylene-9yl)carboxylate into TiO 2 was shown to be complete within 12 fs. 84 The ultrafast transient absorption data mapped the decay of the singlet excited state and the appearance of the oxidized perylene. Nonadiabatic quantum dynamic simulations indicated that injection was complete within 20 fs, in close agreement with the experimental value.…”
Section: Spectroscopymentioning
confidence: 99%
“…The agreement between theory and experiment in these studies indicates that these are powerful tools for quantifying vibronic effects at dye-sensitized interfaces. 84 2.6.2 Sensitizer regeneration. Upon excited-state injection the oxidized sensitizer is reduced by an electron donor present in the electrolyte in a process known as sensitizer regeneration.…”
Section: Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple NA-MD studies of bulk perovskites have been undertaken to date, providing insight into the role of cation and halide identity, symmetry breaking at grain boundaries, and vacancies in determining the kinetics of such processes. Other works have reported NA-MD studies of the nonradiative hot carrier relaxation and electron–hole recombination processes in perovskite nanocrystals, 2D perovskites, and related heterostructure systems. Currently, NA-MD simulations of complex systems such as condensed phase or nanoscale materials, including lead halide perovskites (LHPs), rely on the use of a single-particle (SP) description of the electronic excited states. Within this description, the Coulomb and exchange interactions between electrons and holes are neglected, and the electrons and holes are considered free particles.…”
mentioning
confidence: 99%
“…Differential absorption (Δ mOD) was detected via a 5 kHz chopper, a home-built high-throughput prism polychromator, and a 10 kHz line-scan camera enabling shot-to-shot referencing. IET from several perylene chromophores substituted with different single linkers in the peri position has been investigated by us. , Measured IET times ranged from around 12 fs for a directly bound carboxylic acid linker (Pe-COOH) to 100 fs for a saturated propionic acid linker. Therefore, high time resolution is required for the experiment.…”
Section: Methodsmentioning
confidence: 99%